2003
DOI: 10.1097/00005721-200309000-00013
|View full text |Cite
|
Sign up to set email alerts
|

WIC Providers’ Perspectives on Offering Smoking Cessation Interventions

Abstract: WIC providers have time limitations that may necessitate minimal or low-intensity interventions for smoking cessation, but did not know that such approaches are actually effective. WIC providers require more education about the entire issue of smoking cessation in order to become more proactive in their attempts to help pregnant women quit. Training that enhances self-efficacy and understanding of the impact of smoking on mothers, infants, and children should be initiated to motivate staff to intervene. Anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 14 publications
1
59
0
Order By: Relevance
“…113,133,[162][163][164][165][166][167][168] The synthesis identified that both the professional role of participants and the organisational context in which they worked could act as either barriers to or facilitators of an individual's ability to provide smoking cessation support to pregnant or postpartum women. Underpinning these factors was an acknowledgement that the association between maternal smoking and social disadvantage was a considerable barrier to addressing and supporting smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…113,133,[162][163][164][165][166][167][168] The synthesis identified that both the professional role of participants and the organisational context in which they worked could act as either barriers to or facilitators of an individual's ability to provide smoking cessation support to pregnant or postpartum women. Underpinning these factors was an acknowledgement that the association between maternal smoking and social disadvantage was a considerable barrier to addressing and supporting smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…In those circumstances, promoting harm reduction (cutting down) was prominent and still practised. 162,164,165,167 There was less evidence found of promoting cutting down in the interviews we conducted with UK HPs, although some who were not trained smoking cessation advisors still regarded this as acceptable or helpful, or in some cases inevitable, particularly when dealing with women or families living in complex and disadvantaged circumstances.…”
Section: Organisational Factors Hindering Smoking Cessationmentioning
confidence: 87%
See 2 more Smart Citations
“…4 Similarly, socioeconomic disadvantage is strongly associated with antenatal depression, 11,12 so it is unsurprising that almost 50% of pregnant smokers have depression or other common mental disorders. 10 Smoking cessation programmes in pregnancy reduce the proportion of women who continue to smoke 13,14 and can impact on birth outcomes [15][16][17] so referral from maternity services is emphasised as an important component of antenatal care in current guidelines. 18 Although there is evidence that cessation rates can be significantly lower in people with mental disorders, 19 there has been no research on how mental disorders in pregnancy modify the effectiveness of the current NHS pathway for smoking cessation interventions.…”
Section: Introductionmentioning
confidence: 99%